Effects of astaxanthin on microRNA expression in a rat cardiomyocyte anoxia-reoxygenation model - Xinxin Zhang; Xinxin Zhang; Xinxin Zhang; Min Xu; Min Xu; Shuilin Cai; Bei Chen; Hetong Lin; Hetong Lin; Zhiyu Liu; Zhiyu Liu (Frontiers Media S.A., 2023)
Introduction: The protective effects of astaxanthin against myocardial ischemia-reperfusion injuries are well documented, although the mechanisms are not defined.Methods: The anoxia-reoxygenation injury model was established after astaxanthin treated H9c2 cells for 24 h. Cell viability, lactate dehydrogenase, oxidative stress level and western blot were tested. Secondly, measured the effects of astaxanthin pretreatment on microRNA expression in a rat myocardial cell anoxia-reoxygenation injury model.Results: After anoxia-reoxygenation injury, in a dose dependent manner, astaxanthin increased cell viability, superoxide dismutase and glutathione peroxidase activity, decreased lactate dehydrogenase and malondialdehyde levels, downregulated protein expression of caspase-3, caspase-8, nuclear factor erythroid-2-related factor 2 and heme oxygenase-1, and upregulated the Bcl-2/Bax ratio. High-throughput sequencing and qPCR showed that microRNAs rno-miR-125b-5p and rno-let-7c-1-3p were differentially expressed (|log2| ≥ 0.585, q < 0.1) between the normal, anoxia-reoxygenation, and astaxanthin (1.25 μM) groups. Kyoto Encyclopedia of Genes and Genomes and GO Gene ontology pathway enrichment analyses showed that TNF signaling, axon guidance, NF-κB signaling pathway, and other pathways displayed differentially expressed microRNA target genes associated with myocardial injuries.Discussion: These results suggested that thetarget genes of rno-miR-125b-5p were enriched in inflammation and apoptosis-related signaling pathways. Also, the results imply that simultaneous targeting of these related signaling pathways could significantly prevent myocardial anoxia-reoxygenation injury in the presence of astaxanthin.